Histotripsy for portal vein tumor thrombus in a patient with hepatocellular carcinoma: a case report - Burns, Kevin; Juarez, Tiffany M. (Frontiers in Oncology, 2025)
The presence of portal vein tumor thrombus (PVTT) in patients with hepatocellular carcinoma (HCC) carries a poor prognosis and significantly reduces effective treatment options. Here, we present a case of a 76-year-old male with Barcelona Clinic Liver Cancer stage C (BCLC C) HCC and extensive PVTT who was treated with histotripsy having progressed through both locoregional and systemic therapy. Histotripsy produced rapid cavitation of the tumor thrombus eliciting an imaging response in the process and liver regeneration in the treated segment. This case highlights the feasibility of noninvasive histotripsy as a salvage therapy for PVTT from HCC.